P3.200 Effect of Pregnancy on HIV-1 Disease Progression Among Antiretroviral-Naive HIV-1 Infected Women. (13th July 2013) - Heffron, R A; Donnell, D; Mugo, N; Celum, C; Rees, H; Ngure, K; Were, E; Kiarie, J; Baeten, J M
Abstract : Background: Among HIV-1 infected women who have not initiated full regimen antiretroviral therapy (ART), CD4 counts decline during pregnancy, possibly due to hemodilution. It is unclear if this drop is sustained beyond pregnancy, and if pregnancy results in accelerated HIV-1 disease progression. Methods: In a prospective study among 2269 HIV-1 infected ART-naïve women from 7 countries in East and southern Africa, we examined the effect of pregnancy on HIV-1 disease progression. We used random effects models to compare CD4 and plasma viral load changes between pregnant, postpartum and non-pregnant periods (prenatal periods from women who became pregnant and all periods from women who did not become pregnant). Among women who became pregnant, we compared CD4 counts during prenatal, pregnant, and postpartum periods. Results: Women contributed 3471 person-years and 475 women became pregnant (7.2% of time was pregnant and 6.8% was postpartum). After accounting for baseline levels, CD4 counts were 67.7 cells/mm 3 lower (95% CI 55.5–79.9) during pregnant compared to non-pregnant periods and 81.2 cells/mm 3 lower (95% CI 65.3–97.2) during pregnant compared to postpartum periods. After adjustment for baseline viral load, there were small increases in plasma viral load: a 0.05 log10 increase in pregnant vs. non-pregnant periods (95% CI 0.01–0.10) and a 0.08 log10 increase in pregnant vs. postpartum periods (95% CI 0.01–0.14). Postpartum CD4 and plasma viral loads were not different from non-pregnant periods (p = 0.1 and p = 0.5). Among women who experienced pregnancy, CD4 counts were 59.6 cells/mm 3 lower (95% CI 35.2–84.0) during pregnant versus prenatal periods and 71.6 cells/mm 3 lower (95% CI 48.0–95.1) during pregnant versus postpartum periods. Prenatal and postpartum CD4 counts were similar (p = 0.4). Conclusion: CD4 count and plasma viral load changes among HIV-1 infected women during pregnancy are not permanent and are likely to return to prenatal levels. Pregnancy was not associated with subsequent disease progression.